Severe infections in critically ill solid organ transplant recipients. (December 2018) - Kalil, A.C.; Sandkovsky, U.; Florescu, D.F.
Abstract: Background: Severe infections are among the most common causes of death in immunocompromised patients admitted to the intensive care unit. The epidemiology, diagnosis and treatment of these infections has evolved in the last decade. Aims: We aim to provide a comprehensive review of these severe infections in this population. Sources: Review of the literature pertaining to severe infections in critically ill solid organ transplant recipients. PubMed and Embase databases were searched for documents published since database inception until November 2017. Content: The epidemiology of severe infections has changed in the immunocompromised patients. This population is presenting to the intensive care unit with specific transplantation procedure–related infections, device-associated infections, a multitude of opportunistic viral infections, an increasing number of nosocomial infections and bacterial diseases with a more limited therapeutic armamentarium. Both molecular diagnostics and imaging techniques have had substantial progress in the last decade, which will, we hope, translate into faster and more precise diagnoses, as well as more optimal empirical treatment de-escalation. Implications: The key clinical elements to improve the outcome of critically ill solid organ transplant recipients depend on the knowledge of geographic epidemiology, specific surgical procedures, net state of immunosuppression, hospital microbial ecology, aggressive diagnostic strategy and search for source control, rapid initiation of antimicrobials and minimization of iatrogenic immunosuppression.